2016
DOI: 10.1021/acs.analchem.5b04095
|View full text |Cite
|
Sign up to set email alerts
|

Atomization of Bismuthane in a Dielectric Barrier Discharge: A Mechanistic Study

Abstract: Access and use of this website and the material on it are subject to the Terms and Conditions set forth at Atomization of bismuthane in a novel dielectric barrier discharge: a mechanistic study Kratzer, Jan; Zelina, Ondřej; Svoboda, Milan; Sturgeon, Ralph E.; Mester, Zoltan; Dedina, Jiri NRC Publications Record / Notice d'Archives des publications de CNRC:http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=en http://nparc.cisti-icist.nrc-cnrc.gc.ca/npsi/ctrl?lang=fr READ THESE TERMS AND CONDITIONS CAREFULL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…On the other hand, Kratzer et al found that some memory effects occurred to DBD as an atomizer for bismuthane in the presence of oxygen admixed with argon discharge gas. Moreover, their recent work demonstrated that the DBD atomizer could be employed to trap bismuth on the surface of quartz in the presence of high level selenium, arsenic, and antimony hydrides. Compared with those GPE methods using the heated graphite furnace , or quartz tube, the DBD trapping device could consume less energy due to no electrical heating process, such as only <20 W in this work.…”
mentioning
confidence: 99%
“…On the other hand, Kratzer et al found that some memory effects occurred to DBD as an atomizer for bismuthane in the presence of oxygen admixed with argon discharge gas. Moreover, their recent work demonstrated that the DBD atomizer could be employed to trap bismuth on the surface of quartz in the presence of high level selenium, arsenic, and antimony hydrides. Compared with those GPE methods using the heated graphite furnace , or quartz tube, the DBD trapping device could consume less energy due to no electrical heating process, such as only <20 W in this work.…”
mentioning
confidence: 99%
“…Unlike a previous study, more than 75% of arsenic could be released from the in situ DBD tube at 0 mL/min H 2 , due to possible H 2 introduction from the mixed H 2 –Ar shield gas. During arsenic releasing, H 2 might play an essential role in supplying H radicals for As atomization or ionization …”
Section: Resultsmentioning
confidence: 99%
“…The absolute analytical sensitivity of the previous DBD-AFS/AAS was compromised by unsatisfactory half peak width and the residual analyte in rear nondischarge area of the DBD set. , After optimization of the in situ DBD trap, the half peak width of the in situ DBD trap was compared with that of the original DBD in Figure and Table . The in situ DBD trap presented a sharper peak of 0.3 s from 5 ng of arsenic vs those of HG-AFS (1.3 s) and HG-DBDR-AFS (1.2 s) systems from 20 ng of arsenic with similar peak heights.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations